2010
DOI: 10.1007/s10753-010-9256-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism on Cytokines Expression in the Temporomandibular Joint: The Role of Gonadal Steroid Hormones

Abstract: Temporomandibular joint pain-related conditions are generally characterized by local inflammation; however, little studies have focused on the role of gonadal hormones in the expression of inflammatory mediators, such as cytokines. Therefore, we asked whether gonadal steroid hormones affect formalin-induced cytokines expression in the rat temporomcandibular joint. The expression of tumor necrosis factor alpha (TNF-α), interleukin (IL)-1β, and cytokine-induced neutrophil chemoattractant (CINC)-1 was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
12
1
1
Order By: Relevance
“…In our study, we found that with increased 17β‐estradiol, IL‐8Rβ expression was upregulated and other have demonstrated that upregulation of IL‐8Rβ causes Ca 2+ ‐regulated opioid release from polymorphonuclear cells and thereby inhibits inflammatory pain (Rittner et al, 2006). In addition, studies have also shown other cytokines such as IL‐6 (Yun et al, 2008; Torres‐Chavez et al, 2010), IL‐1β and IL‐8 (Yun et al, 2008) are modulated in the TMJ tissues after estrogen administration. Our study did not observe any affect on these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that with increased 17β‐estradiol, IL‐8Rβ expression was upregulated and other have demonstrated that upregulation of IL‐8Rβ causes Ca 2+ ‐regulated opioid release from polymorphonuclear cells and thereby inhibits inflammatory pain (Rittner et al, 2006). In addition, studies have also shown other cytokines such as IL‐6 (Yun et al, 2008; Torres‐Chavez et al, 2010), IL‐1β and IL‐8 (Yun et al, 2008) are modulated in the TMJ tissues after estrogen administration. Our study did not observe any affect on these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines measurement was performed as previously described (Torres-Chavez et al, 2011). Prior to the assay, hind paw tissue was homogenized in phosphate buffered saline (PBS, pH ¼ 7.4) containing 0.4 M NaCl, 0.05% Tween-20, 0.5% bovine serum albumin, 0.1 mM phenylmethylsulfonyl fluoride, 0.1 M benzethonium chloride, 10 mM EDTA and 20 kl/mL aprotinin.…”
Section: Cytokines Measurementmentioning
confidence: 99%
“…In ovariectomized rats, amygdala implant of both progesterone and estradiol heightened the responsiveness to colorectal distension, suggesting a central modulation of visceral pain induced by female hormones [13]. Moreover, both female hormones modulate mediators such as cytokines in the rat temporomandibular joint (TMJ) [14]. In analogy with estrogens, progesterone showed both pronociceptive and antinociceptive effect, given that it was able to reduce allodynia in neuropathic pain after spinal cord injury [15], but increased hyperalgesia in male and ovariectomized female rats [16].…”
Section: Role Of the Gonadal Hormones In Brain Function And Painmentioning
confidence: 99%